Drivers of game species depletion in sustainable-use protected areas of the Brazilian Amazon - Sampaio, Ricardo (2021)
A considerable portion of tropical protected areas are Sustainable-Use Reserves (SURs), where human settlements and sustainable natural resource extraction are legally permitted. Hunting on game species is widespread in tropical forests, that can deplete game populations within SURs and to reduce their effectiveness on biodiversity conservation. In this doctoral thesis, based on data from nine SURs located in the central and southwestern portion of Brazilian Amazon, I evaluated if the local hunter\'s perception about local game abundance change (chapter I), the local and regional occurrences of terrestrial game species (chapter II) and their relative abundances (chapter III) are affected by hunting pressures exerted by local communities and urban areas, the local level of protection and variables considering local environmental quality. The negative impacts of hunting on game species were reduced in human communities having more access to aquatic protein, with reduced wildmeat urban demand (farther from the cities) and with lower habitat loss in their vicinities. The local level of protection showed a positive effect in the local game abundance change perceived by local hunters, however the relative abundances of two hunt-sensitive species, estimated by camera traps, were reduced inside SURs. The results provide valuable information to support evidence-based conservation strategies in tropical forests that should prioritize: (1) the reduction of wild meat urban demand; (2) the management of local aquatic animal protein in floodplain areas to relieve pressure on terrestrial game species; (3) the implementation of community-based management plans for subsistence hunting in human communities (i) inside protected areas; (ii) closer to urban areas; (iii) with higher dependency of terrestrial protein, and; (iv) with higher levels of habitat loss in the catchment areas around them.